Physiological effects of indigenous arbuscular mycorrhizal associations on the sclerophyll Agathosma betulina (Berg.) Pillans - Cloete, Karen Jacqueline (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2005.